Prussian blue [compact disc, unabridged] : a Bernie Gunther novel - Kerr, Philip (Kerr, Philip. Bernie Gunther novel., 2017)
When his cover is blown, Bernie Gunther plays a game of cat-and-mouse with an old enemy before escaping to Berlin seeking help from a group of former allies.